Cognitive Pocket Method Application in Education of Children with ASD - Zavarzina-Memmi E.G (Moscow State University of Psychology and Education, 2018)
A description of the author's Cognitive Pocket Method is given, which is primarily intended for work with children with autism spectrum disorders and, generally, involves parents or tutor individual lessons with a child. The Cognitive Pocket Method allows to adjust the auditory perception, respectively - the understanding of oral speech, and teach to read as well. Also the method subsequently provides to the wards education and communication techniques. The method can be used with normotupical children and adults, it is used both at home and in the specialist's environment, which includes application in the group of children. Alongside with the solution of the main tasks associated with auditory perception, the Cognitive Pocket Method trains attention, memory (including motor), visual skills (depth of field, eye control of hand actions), coordination, fine motor skills, touch, motor planning.